Analisis Deiksis Pada Cerpen “Dilarang Menyanyi Di Kamar Mandi” Karya Seno Gumira Ajidarma - Dea Puspita Sari (Morfologi : Jurnal Ilmu Pendidikan, Bahasa, Sastra dan Budaya, 2024)
This research aims to describe the use of deixis in literary works, especially short stories. The use of deixis is quite important in the process of interaction and communication, including in short stories which are quite dense in writing because they are related to indicating something and leading to certain references or points of reference and are bound by the context of the utterance. The data for this research is in the form of deixis data originating from the short story "It is forbidden to sing in the bathroom" by Senoo Gumira Ajidarma. The research method used is content analysis with stages of data collection, sample determination, data recording, data reduction, drawing conclusions from the data, and deictic analysis contained in the short story. The research results include six sentences for first person deixis, one sentence for third person deixis or more than one. In existence there is one sentence. In the discourse diexis there are three sentences, and in the social diexis there is also one conversational sentence.